Perioperative Inflammatory Response and Cancer Recurrence in Lung Cancer Surgery: A Narrative Review - Choi, Hoon; Hwang, Wonjung (Frontiers in Surgery, 2022)
While surgical resection is a gold standard treatment in solid tumors, cancer recurrence after surgery is common. Immunosurveillance to remnant tumor cell is an important protective mechanism. Therefore, maintaining anti-tumor cell activity and proper level of inflammatory mediators are crucial. Accumulating evidence suggests that surgery itself and perioperative interventions could affect these pathophysiological responses. Various factors, such as extend of tissue injury, perioperative medications including anesthetics and analgesics, perioperative management including transfusion and methods of mechanical ventilation, modulate the inflammatory response in lung cancer surgery. This narrative review aims to summarize the pathophysiological mechanism involved in cancer recurrence after surgery and perioperative management related to cancer recurrence after lung cancer surgery.